POSSIBILITIES OF THE COMPUTED TOMOGRAPHY METHOD IN THE DIAGNOSIS OF CENTRAL LUMBAR SPINAL CANAL STENOSIS - Turgunov Shomakhmud Shomansurovich; Ablyazov Aduvakhob Abdumazhidovich; Ablyazov Otabek Vakhobovich; Nurmatova Mashhura Mukhammadjon kizi (Web of Journals Publishing, 2024)
To date, a large number of fundamental works have accumulated, the analysis of which shows that lumbar vertebral central stenosis is a fairly common disease among the general pathology of the spine. Central stenosis is a consequence of various pathogenetic processes of the bone and soft tissue components of the lumbar spinal canal, and is mainly diagnosed by radiation methods. One of which is the CT method, discovered in 1972. The creation of spiral (CT) and multispiral (MSCT) computed tomographs has made the CT method extremely reliable and universal for early diagnosis and screening of central spinal canal stenosis. CT with CT and MSCT using three-dimensional reconstruction, having a high scanning speed, the ability to cover a significant length of the spine, visualizes the initial changes in the intervertebral disc, differentiates the structures of the spinal canal, the magnitude of the prolapse of the disc into the canal, the magnitude and migration of sequesters, their “age", i.e. It gives a more complete picture of degenerative-dystrophic diseases of the lumbar spine, including central spinal canal stenosis as a result of lesions of the bone and soft tissue structures of the spine. The possibility of visualization of spinal pathology allows us to consider CT as the main and most accessible diagnostic method for vertebral and discogenic lesions, with which it is possible to identify with high accuracy the pathological changes that cause central stenosis of the lumbar spinal canal. CT with CT and MSCT has been perceived by many scientists as the biggest step forward in radiation diagnostics since the discovery of X-rays. The purpose of the study: To study the possibilities of computed tomography in establishing the diagnosis of lumbar vertebral stenosis.